Asymmetries in the transmission of monetary policy shocks over the business cycle: A Bayesian Quantile Factor Augmented VAR - Sofia Velasco (European Central Bank (ECB), 2024)
This paper introduces a Bayesian Quantile Factor Augmented VAR (BQFAVAR) to examine the asymmetric effects of monetary policy throughout the business cycle. Monte Carlo experiments demonstrate that the model effectively captures non-linearities in impulse responses. Analysis of aggregate responses to a contractionary monetary policy shock reveals that financial variables and industrial production exhibit more pronounced impacts during recessions compared to expansions, aligning with predictions from the "financial accelerator" propagation mechanism literature. Additionally, inflation displays a higher level of symmetry across economic conditions, consistent with households' loss aversion in the context of reference-dependent preferences and central banks' commitment to maintaining price stability. The examination of price rigidities at a granular level, employing sectoral prices and quantities, demonstrates that during recessions, the contractionary policy shock results in a more pronounced negative impact on quantities compared to expansions. This finding provides support for the notion of stronger downward than upward price rigidity, as suggested by "menu-costs models".
Keywords: C11 C32 E32 E37 E52; 330; Bayesian Quantile VAR; FAVAR; Asymmetric effects of monetary policy; Disaggregate prices; Non-linear models